1994
DOI: 10.1038/bjc.1994.428
|View full text |Cite
|
Sign up to set email alerts
|

How accurate are Scottish cancer registration data?

Abstract: SinaryIn order to assess the accuracy of Scottish cancer registration data, a random sample of 2,200 registrations, attributed to the year 1990, was generated. Relevant medical records were available for review in 2,021 (92%) cases. Registration details were reabstracted from available records and compared with data in the registry. Discreancies in identifying items of data (surname, forename, sex and date of birth) were found in 3.5% of cases. Most were trivial and would not disturb record linkage. Discrepanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 15 publications
1
35
1
Order By: Relevance
“…The quality indicators for registration of head and neck cancer tumours at the Scottish Cancer Registry are high, with approximately 85% of cases being microscopically confirmed and less than 2% Death Certificate Only registrations [21,22]. Moreover, several studies have provided evidence of the high, and constantly improving, case-ascertainment [23][24][25]. The limitations of this study include the lack of data on tumour HPV positivity, behavioural factors (e.g.…”
Section: Discussionmentioning
confidence: 92%
“…The quality indicators for registration of head and neck cancer tumours at the Scottish Cancer Registry are high, with approximately 85% of cases being microscopically confirmed and less than 2% Death Certificate Only registrations [21,22]. Moreover, several studies have provided evidence of the high, and constantly improving, case-ascertainment [23][24][25]. The limitations of this study include the lack of data on tumour HPV positivity, behavioural factors (e.g.…”
Section: Discussionmentioning
confidence: 92%
“…The quality of cancer registry data in Scotland is also believed to be high, both in terms of accuracy (Brewster et al, 1994) and ascertainment (Brewster et al, 1997). The method of record linkage used in Scotland is estimated to result in mismatched records in less than 2% of cases (Kendrick and Clarke, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Scottish National Cancer Registry data are highly reliable, 28 since they are acquired from 3 independent sources: pathology returns, hospital patient coding data and death certificates. Indeed, in the present study, there was only 1 patient identified through hospital or pathology records who was not identified by the Registry.…”
Section: Identification Of the Under-30 Cohortmentioning
confidence: 99%